Acculturation, Religiosity, and Ethnicity Predict Mothers’ Causal Beliefs About Separation Anxiety Disorder and Preferences for Help-Seeking - Sood, Erica D. (Journal of cross-cultural psychology, 2012)
This study examined causal beliefs about separation anxiety disorder (SAD) and preferences for help-seeking among 117 Indian American, Puerto Rican, and European American mothers. Mothers completed measures of acculturation and strength of religious faith (SORF) and, after reading vignettes describing SAD, made judgments about the etiology of symptoms and the likelihood of various forms of help-seeking for youth SAD symptoms. Hierarchical multiple regressions revealed that acculturation to mainstream American culture and SORF predicted mothers’ causal beliefs and preferences for help-seeking. In addition, Puerto Rican mothers were more likely than European American mothers to attribute symptoms to medical causes after accounting for cultural variables. Results highlight the importance of examining cultural constructs that contribute to ethnic group differences. Implications for future research and clinical practice are discussed.